Third Periodic Monitoring Report on the Status of Implementation Plans in Response to Board-Endorsed IEO Recommendations. (Policy Papers; Policy Paper ;, 2009)
Periodic Monitoring Reports (PMRs) were established by the Executive Board in January 2007 to ensure the systematic monitoring of those IEO recommendations that the Board has endorsed. The first PMR was discussed by the Executive Board in January 20081 and the second PMR was discussed by the Evaluation Committee (EVC) in November 2008.2 This third report updates the status of the performance benchmarks related to IEO evaluations covered in the first and second PMRs and listed in Periodic Monitoring Report on the Status of Implementation Plans in Response to Board-Endorsed IEO Recommendations, Table 5. It also updates the implementation status of the management implementation plan (MIP) for Board-endorsed recommendations stemming from the IEO evaluation of "Structural Conditionality in IMF-Supported Programs.".